Efeito do tratamento da H. pylori na expressão de citocinas e microRNAs associados ao processo inflamatório - Rossi, Ana Flávia Teixeira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Persistent infection by Helicobacter pylori (H. pylori) promotes chronic inflammation resulting in damage to the mucosa and the consequent development of gastric lesions as chronic gastritis. This bacterium and its virulence factors vacA and cagA influence the host immune response, deregulating the expression of inflammatory mediators and microRNAs (miRNAs), and activate pathways related to carcinogenic process. Thus, H. pylori eradication may have a key role to reverse precursor lesions, preventing malignant transformation. In the present study evaluated whether the eradication therapy of bacterium influences the mRNA and protein expression of inflammatory mediators (TNFA, IL6, IL1B, IL12A, IL2 and TGFBRII) and miRNAs (hsa-miR-103a-3p, hsa-miR-181c-5p, hsa-miR-370-3p, hsa-miR-375 and miR-223-3p) in H. pylori-positive chronic gastritis patients (Hp+) and compared with non-infected gastritis patients (Hp-). We also evaluated the relationship between the expression levels of miRNAs with of mRNA and protein and participation in interaction networks, as well as the influence of bacterial virulence factors cagA and vacA on these mediators. Relative quantification (RQ) of mRNA and miRNAs was performed by qPCR-real time using TaqMan® assay in 20 patients Hp- and 31 Hp+, which were also evaluated three months after eradication treatment of the bacterium. Genotyping of cagA and vacA was performed by PCR, while the protein expression was assessed by immunohistochemistry. Hp+ patients showed increased mRNA levels for TNFA, IL6, IL1B and IL12A, while for IL2 and TGFBRII as well as for the miRNAs miR-103, miR-181c, miR-370 and miR-375 it were decreased. After treatment, only TNFA and IL6 mRNA were significantly reduced and TGFBRII increased in eradicated patients (p<0.05). On the other hand, all miRNAs, except to miR-223, were significantly increased after bacterium eradication (p<0.05). In general, the...

Infecção persistente pela Helicobacter pylori (H. pylori) promove inflamação crônica que resulta em danos na mucosa e o consequente desenvolvimento de lesões gástricas, como a gastrite crônica. Esta bactéria e seus fatores de virulência vacA e cagA influenciam na resposta imune do hospedeiro, desregulando a expressão de mediadores inflamatórios e microRNAs (miRNAs), assim ativando vias relacionadas ao processo carcinogênico. Portanto, a erradicação da H. pylori pode ter um papel importante para reverter lesões precursoras, prevenindo a transformação maligna. O presente estudo avaliou a influência da terapia de erradicação da bactéria na expressão do RNAm e da proteína de mediadores inflamatórios (TNFA, IL6, IL1B, IL12A, IL2 e TGFBRII) e de miRNAs (hsa-miR-103a-3p, hsa-miR-181c-5p, hsa-miR-370-3p, hsa-miR-375 e miR-223-3p) em pacientes com gastrite crônica H. pylori positivos (Hp+), em comparação com pacientes com gastrite não infectados (Hp-). Também avaliou a relação entre os níveis de expressão dos miRNAs e os dos RNAm e proteínas e a participação em redes de interação, assim como a influência dos fatores de virulência bacteriano cagA e vacA sobre estes mediadores. A quantificação relativa (RQ) do RNAm e dos miRNAs foi realizada por PCR quantitativa em tempo real (qPCR) usando ensaio TaqMan® em 20 pacientes Hp- e 31 Hp+, os quais foram também avaliados três meses após o tratamento de erradicação da bactéria. A genotipagem de cagA e vacA foi realizada pela técnica de PCR, enquanto que a expressão protéica foi avaliada por imuno-histoquímica. Pacientes Hp+ apresentaram níveis aumentados do RNAm de TNFA, IL6, IL1B e IL12A, enquanto que IL2 e TGFBRII bem como os miRNAs miR-103, miR-181c, miR-370 e miR- 375 mostraram expressão reduzida. Após o tratamento, o RNAm de TNFA e IL6 apresentouse significantemente reduzido e de TGFBRII aumentado em pacientes...
Keywords: Genetica humana; Expressão gênica; Helicobacter pylori; Mucosa gastrica - Inflamação; MicroRNAs; Citocinas